Tobacco Consumption Pattern of Selected Districts of Gujarat - Rinkal B Viradiya; Jay R Patwa; Nilesh G Patel (Medsci Publications, 2020)
Background: Globally, among the leading preventable causes of premature deaths tobacco stands on the top. The consumption patterns of tobacco in various forms of chewing and smoking vary across different regions and socioeconomic levels. Objectives: To study tobacco consumption pattern in two districts of Gujarat and compare among them. Methodology: A cross sectional study was carried out on 504 participants during January 2015 to September 2016 among 15-64 years age group. A pre designed and pre tested Questionnaire was used to collect data on tobacco consumption pattern. Descriptive and analytical statistical methods were used for the data analysis. Results: Smoking was reported among 11.51% and 18.25% in Gandhinagar and Mehsana district respectively. Out of which around 90% of them in both district were smoking daily. 34.52% of the studied population in Mehsana district was using smokeless tobacco as compared to Gandhinagar district (26.19%). Initiation of smoking was in later age as compared to smokeless tobacco. Conclusion: Present study concludes that large number of people including younger population was using smokeless tobacco in both districts. Early initiation of use of smokeless tobacco suggests an urgent need for action.